Succesful Continuous Renal Replacement Therapy (CRRT) for Acute Kidney Injury (AKI) with Septic Shock Underwent Long Coronary Artery Bypass Graft Procedure (CABG) - Pertiwi, Previasari Zahra; Fatoni, Arie Zainul; Agustina, Ayu Yesi; Jaya, Wiwi (Faculty of Medicine, Brawijaya University, 2024)
Background :AKI occurs in significant numbers of patients undergoing cardiopulmonary bypass surgery for coronary artery disease. Patient with AKI requiring renal replacement therapy (RRT) after cardiac surgery were at a higher risk of postoperative mortality. One of mode of RRT is CRRT. CRRT can keep hemodynamic of the patient stable, excellent control of azotemia, sypport beneficial immunomodulation,increase clearance of inflammatory mediators and potentially less ongoing or repeated renal ischaemia. As an alternative to traditional intermittent hemodialysis, CRRT has now emerged as the leading form of RRT for patients with AKI post CABG because the CRRT can keep hemodynamic still stable.Case: We report a case report of patient who had long aorta cross clamp in CABG procedure. He got AKI with shock condition during hospitalization in ICU, had been done with CRRT and had good response after the procedure.Discussion: The incidence of AKI after cardiac surgery in this patient may increase with several risk factors, such as surgical bleeding, diabetes mellitus, pre operative renal dysfunction, low LVEF, the use of CPB machine and infection. An imbalance between renal oxygen supply and oxygen demand will induce AKI. This patient had done CRRT and showed good clinical and laboratory condition after that. Conclusion : CRRT is a good choice for AKI patient post CABG procedure with shock condition.